The effect of product variation strategies premium pricing marketing communication and digital marketing on marketing performance - Maria Susana Elaman; Yolinda Yanti Sonbay; Gaudensius Djuang; Simon Sia Niha; Anggraeny Paridy (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of product variation strategies, premium pricing, marketing communication, and digital marketing on marketing performance. Conducted this research in Malaka, East Nusa Tenggara. A population of 50 respondents. The analytical method used SPSS 15.00. This result rejects the proposed hypothesis, which is quite good. Consumer perceptions of product variety strategies, premium pricing, marketing communication and digital marketing at BUMDes Kufeu-M'rian-Malaka are good. The results showed that all strategies carried out had a positive and significant effect on marketing performance. Premium pricing has a positive and significant effect on the marketing performance of BUMDes Kufeu-M'rian-Malaka.